2021
DOI: 10.3389/fmicb.2021.780759
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing Regulates the Hydrolytic Enzyme Production and Community Composition of Heterotrophic Bacteria in Coastal Waters

Abstract: Heterotrophic microbial communities play a central role in biogeochemical cycles in the ocean by degrading organic matter through the synthesis of extracellular hydrolytic enzymes. Their hydrolysis rates result from the community’s genomic potential and the differential expression of this genomic potential. Cell-cell communication pathways such as quorum sensing (QS) could impact both aspects and, consequently, structure marine ecosystem functioning. However, the role of QS communications in complex natural as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Van Mooy et al (2012) made similar observations in epibiontic bacteria colonizing Trichodesmium colonies, demonstrating that the addition of C8-, 3-oxo-C8-HSL and long-chain AHLs (a cocktail of C10-, C12-and C14-HSL) induced a doubling of extracellular alkaline phosphatase activity (total activity). Finally, Urvoy et al (2021b) showed that the addition of low concentrations of C4-, C6-, 3-oxo-C8-, C12-or C16-HSL to coastal bacterioplankton communities sampled in two contrasting stages of the spring phytoplankton bloom differently modified their extracellular leucine aminopeptidase, N-acetyl glucosaminidase, lipase and β-glucuronidase activities (total activity), further highlighting the complexity of QS regulation.…”
Section: Quorum Sensing Directly Impacts Organic Matter Degradation C...mentioning
confidence: 96%
See 4 more Smart Citations
“…Van Mooy et al (2012) made similar observations in epibiontic bacteria colonizing Trichodesmium colonies, demonstrating that the addition of C8-, 3-oxo-C8-HSL and long-chain AHLs (a cocktail of C10-, C12-and C14-HSL) induced a doubling of extracellular alkaline phosphatase activity (total activity). Finally, Urvoy et al (2021b) showed that the addition of low concentrations of C4-, C6-, 3-oxo-C8-, C12-or C16-HSL to coastal bacterioplankton communities sampled in two contrasting stages of the spring phytoplankton bloom differently modified their extracellular leucine aminopeptidase, N-acetyl glucosaminidase, lipase and β-glucuronidase activities (total activity), further highlighting the complexity of QS regulation.…”
Section: Quorum Sensing Directly Impacts Organic Matter Degradation C...mentioning
confidence: 96%
“…The possible role of QS in synchronizing hydrolase expression in bacteria would impact C, P, and N cycles through the degradation of various polymers. Several studies have examined the implications of QS in hydrolase expression in either isolated strains (Jatt et al, 2015;Su et al, 2019;Urvoy et al, 2021a) or natural bacterial communities from various environments (Hmelo et al, 2011;Van Mooy et al, 2012;Krupke et al, 2016;Su et al, 2019;Urvoy et al, 2021b; Supplementary Table 4). These studies, mainly performed in the context of AHL-based QS, have largely demonstrated the complexity of QS regulation, as no clear pattern has emerged.…”
Section: Quorum Sensing Directly Impacts Organic Matter Degradation C...mentioning
confidence: 99%
See 3 more Smart Citations